2018
DOI: 10.1029/2018gl077972
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Iron, Cobalt, and Vitamin B12 Supply on Phytoplankton Growth in the Tropical East Pacific During the 2015 El Niño

Abstract: Iron (Fe), cobalt (Co), and vitamin B 12 addition experiments were performed in the eastern Equatorial Pacific/Peruvian upwelling zone during the 2015 El Niño event. Near the Peruvian coastline, apparent photosystem II photochemical efficiencies (F v /F m ) were unchanged by nutrient addition and chlorophyll a tripled in untreated controls over 2 days, indicating nutrient replete conditions. Conversely, Fe amendment further away from the coastline in the high nitrate, low Fe zone significantly increased F v /F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 69 publications
(119 reference statements)
3
16
0
Order By: Relevance
“…In our simulations, iron limitation occurred offshore over a larger area of the domain and closer to the coast in the submesoscale-permitting simulation (not shown), suggesting that iron may be even more strongly affected by the subduction associated with submesocale filaments and fronts than NO 3 . This is in line with recent findings of Browning et al (2018), who observed iron limitation of phytoplankton growth between 73 km -266 km from the Peruvian coastline, in contrast with nutrient replete conditions 26 km from the coast on the shelf. The authors conclude that iron is likely an important factor driving reductions in offshore phytoplankton productivity in the PCUS.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In our simulations, iron limitation occurred offshore over a larger area of the domain and closer to the coast in the submesoscale-permitting simulation (not shown), suggesting that iron may be even more strongly affected by the subduction associated with submesocale filaments and fronts than NO 3 . This is in line with recent findings of Browning et al (2018), who observed iron limitation of phytoplankton growth between 73 km -266 km from the Peruvian coastline, in contrast with nutrient replete conditions 26 km from the coast on the shelf. The authors conclude that iron is likely an important factor driving reductions in offshore phytoplankton productivity in the PCUS.…”
supporting
confidence: 93%
“…on models and comparison to observations has proven difficult, due to the difficulties of observing vertical velocities. Also, iron is known to play a role in limiting primary production in the PCUS (Hutchins et al, 2002;Bruland et al, 2005;Browning et al, 2018) which previous model studies have not addressed with respect to eddy-fluxes of biogeochemical tracers. Regional simulations are often mainly validated using surface chlorophyll maps derived from ocean color, which does not allow to assess the underlying physical (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…a), to year‐round N limitation in the subtropical gyre to the south (Graziano et al ; Blain et al ; Moore et al , ; Nielsdóttir et al 2009; Ryan‐Keogh et al ). Accordingly, transitions in the primary limiting nutrients, between either N or Fe, were in turn predictable on the basis of the initial concentrations of nitrate alone, the dissolved ratio of nitrate to Fe (i.e., N:Fe), or calculated values of Fe* (see Table ; Browning et al , , ; Moore ). Conditions approaching N‐Fe co‐limitation were also apparent in Experiments 2 and 6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is true that we only measure the effect on bulk phytoplankton and bacteria, and thus we have toned down all the conclusions about the effect on microbial community structure. We do not think that is unfortunate to have chosen phytoplankton and bacterial biomass as response variable, considering that most previous studies evaluating the role of B vitamins were based on biomass measurements (Sañudo-Wilhelmy et al, 2006;Gobler et al, 2007;Koch et al, 2011Koch et al, , 2012Browning et al, 2018;Barber-Lluch et al, 2019). We are aware of many variables that could affect bacterial and phytoplankton biomass, for this reason, we compared the response of B vitamin treatments with their corresponding controls.…”
Section: C2mentioning
confidence: 99%